2023
DOI: 10.1186/s12882-023-03338-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of urinary tract infection in kidney recipients: a meta-analysis study

Masoumeh Hosseinpour,
Aiyoub Pezeshgi,
Morteza Zaboli Mahdiabadi
et al.

Abstract: Background A kidney recipient's urinary tract infection (UTI) can result in infectious problems and be a risk factor for less successful transplant outcomes. UTI risk factors are still controversial. The present study aimed to investigate the prevalence of UTI and its association with risk factors in kidney recipients. Method Twenty-six papers published between 2005 and 2022 were retrieved using keywords and searching Medlib, ScienceDirect, PubMed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…This has been well investigated in a work from Brazil in 2022, where, in line with the later studies, higher age was associated with an increased risk for more UTIs (approximate risk of UTI of 3.6% per year of age) [ 22 ▪▪ ]. Another large meta-analysis from 2023 including 72 600 KTX patients confirmed these results, showing a 3% increase in the odds of experiencing a UTI with each year of age [ 23 ▪▪ ]. However, when looking at some newer studies, such as one from Al Tamimi et al in 2023, age categories including the age >60 were not associated with a higher risk of UTIs [ 24 ].…”
Section: Influence Of Age On Urinary Tract Infectionsmentioning
confidence: 86%
See 2 more Smart Citations
“…This has been well investigated in a work from Brazil in 2022, where, in line with the later studies, higher age was associated with an increased risk for more UTIs (approximate risk of UTI of 3.6% per year of age) [ 22 ▪▪ ]. Another large meta-analysis from 2023 including 72 600 KTX patients confirmed these results, showing a 3% increase in the odds of experiencing a UTI with each year of age [ 23 ▪▪ ]. However, when looking at some newer studies, such as one from Al Tamimi et al in 2023, age categories including the age >60 were not associated with a higher risk of UTIs [ 24 ].…”
Section: Influence Of Age On Urinary Tract Infectionsmentioning
confidence: 86%
“…The inconsistency in findings among studies may be due to variations in study populations, methodology, and most importantly age category definitions [ 25 ▪▪ ]. To sum up increasing age was confirmed as significant risk factor in six studies [ 3 ▪▪ , 11 ▪▪ , 22 ▪▪ , 23 ▪▪ , 25 ▪▪ , 28 ] comparing to three [ 24 , 29 , 30 ] studies failing to prove this association.…”
Section: Influence Of Age On Urinary Tract Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This nding is consistent with global and Indian studies, which have consistently reported a predominance of gram-negative bacteria, particularly E. coli and Klebsiella species, in UTIs among renal transplant recipients. [24,25] However, the study also reported a concerning trend of antimicrobial resistance, with 12% of isolates being multi-drug resistant (MDR) and 7% being pan-drug resistant (PDR). This nding aligns with the growing global challenge of antimicrobial resistance, which can complicate the management of UTI and contribute to adverse outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Common risk factors include prolonged indwelling catheters and Double J stents after transplantation, premature discontinuation of antibiotics, short length of transplant ureter, absence of sphincter between transplant ureter and native bladder, and net high dose of immunosuppression immediately post-transplant 57 . Risk factors for recurrence include older age, female donor, deceased donor, neurogenic bladder, history of preoperative UTI, and acute rejection episodes (treated with steroids or immunosuppressive regimens) 57 . Recurrent UTIs have been reported to occur in 4%-72% of transplant recipients 8 .…”
Section: Introductionmentioning
confidence: 99%